Enhancing the filtration performance of common substrates used in the Covid-19 respiratory protection equipment with nanofiber coatings - Mobina Khezrian; Adel Jafari; Majid Habibi Mohraz (Heliyon)
With the emergence of the COVID-19 pandemic, there has been a significant increase in the demand for facemasks as an effective means of protection. As a result, a variety of materials, including woven and nonwoven fabrics, have been utilized as filtration mediums in respiratory protection equipment (RPEs). However, many of these RPEs, despite their widespread use, do not provide adequate protection against aerosols and bioaerosols. Recent studies have demonstrated that nanofiber coatings possess properties that can enhance the protective capabilities of RPEs.The purpose of this study was to investigate the effects of applying nanofiber coatings on the filtration properties of common substrates used in RPEs. Specifically, polyacrylonitrile (PAN) and PAN modified with CuBTC nanofibers (PAN/CuBTC) were coated onto seven common types of substrates used in RPEs: two types of melt-blown fabric with grammages of 15 and 25 g/m2, two types of spunbond fabric with grammages of 25 and 30 g/m2, SSMMS fabric with a grammage of 25 g/m2, activated carbon fabric, and Tetron fabric. The initial filtration efficiency, pressure drop, and quality factor of the prepared media were then measured.The results clearly indicated that the application of PAN and PAN/CuBTC nanofiber coatings significantly enhances the filtration efficiency of all examined substrate layers, achieving efficiencies exceeding 90 % and 95 % at the most penetrating particle size (MPPS, 300 nm), respectively.The assessment of the quality factor revealed that the highest quality factor values before and after coating with PAN and PAN/CuBTC nanofibers corresponded to the SSMMS substrates, with values of 0.023, 0.072, and 0.094 Pa⁻1, while the lowest quality factor values were associated with Tetron, which had values of 0.002, 0.016, and 0.021 Pa⁻1, respectively.The comparison of various substrates revealed that the SSMMS fabric exhibited the highest quality factor after coverage with nanofibers, while the Tetron fabric demonstrated the lowest quality factor.Based on the quality criteria, the SSMMS fabric was the best substrate for nanofiber coatings, followed by melt-blown, spun bond, and activated carbon fabrics, whereas the Tetron fabric was not recommended for this application due to a high respiratory pressure drop.